ANALISIS PENGENDALIAN KUALITAS PRODUK KERTAS DENGAN METODE STATISTICAL QUALITY CONTROL PADA PT ADIPRIMA SURAPRINTA GRESIK - Muhammad Fahmi Idris; Istantyo Yuwono (LPPM Universitas Bina Bangsa, 2023)
PT Adiprima Suraprinta is a subsidiary of Jawa Pos Group which is located in Sumengko Village, Wringinanom, Gresik. PT. Adiprima Suraprinta was founded in 1997, this factory is one of the industrial companies in Indonesia that produces paper. With paper industry competition being very tight, PT Adiprima Suraprinta needs to innovate and pay attention to the quality of its products to maintain stability in quality in order to become the leading paper company in Indonesia. Based on the results of the research and discussion analysis that has been described, it is known that the production of News Print Paper type newsprint in the 2022 period is 52174 Tons with defective conditions that occur in production of 14633 Tons of copies. The average defect in each production in a one-month period is 30%. in several production times there were defects that exceeded the target of the number of production. The analysis method used is check sheet, control chart, pareto and fishbone. This is based on observations made where damage to newsprint paper occurs during the production process using the company's Paper Mill machine where each machine is run by several operators. Therefore, efforts to overcome the occurrence of defects caused by these factors can be carried out by providing training to workers, creating a new work appraisal system with the aim of motivating workers' performance to be better. Checking the readiness of the machine before and after use so that it is in accordance with operational standards and Immediately replace damaged engine components so that they do not hinder the production process